Morphometric and genetic characterization of tilapia (Cichlidae: Tilapiini) stocks for effective fisheries management in two mexican reservoirs - Verónica Espinosa-Lemus (Hidrobiológica, 2009)
Several tilapia species were introduced to the Infiernillo Dam during the 1960's. Following this introduction of tilapia, the dam has been an important fish production site in Mexico. However, recent decreases in tilapia catches suggest that fish management strategies and tilapia exploitation practices need to be revised. To date, management practices are limited by the lack of methods to evaluate the status of these introduced species. Here we morphometrically characterized two genera and three species from two sites in the Infiernillo Dam and a site in the Zicuiran Dam. The samples were characterized for 14 allozyme loci and two mitochondrial DNA-RFLP markers, r16S and cytochrome b. Based on these morphological and genetic markers, we identified Tilapia rendalli and Oreochromis aureus in the InfiernilloDam, and Oreochromis mossambicus at the Zicuiran reservoir. These species were separated into genera based on differences in the number of predorsal scales and the pharyngeal teeth morphology. For Oreochromis, they were further classified into species using six morphometric variables. The allozyme and mtDNA-RFLP results are concordant with the morphological differences. Furthermore, two populations of O. aureus in the Infiernillo Dam appear genetically and morphologically distinct. The levels of genetic variability (He = 0.0567-0.2299 and h = 0.0000-0.4848) are low compared to properly managed tilapia populations. Given the levels of variation in these populations, we suggest sustainable genetic management strategies.